Locally Excited State–Charge Transfer State Coupled Dyes as Optically Responsive Neuron Firing Probes. Issue 58 (18th September 2017) - Sirbu, Dumitru; Butcher, John B.; Waddell, Paul G.; Andras, Peter; Benniston, Andrew C.
Abstract: A selection of NIR‐optically responsive neuron probes was produced comprising of a donor julolidyl group connected to a BODIPY core and several different styryl and vinylpyridinyl derived acceptor moieties. The strength of the donor–acceptor interaction was systematically modulated by altering the electron withdrawing nature of the aryl unit. The fluorescence quantum yield was observed to decrease as the electron withdrawing effect of the aryl subunit increased in line with changes of the Hammett parameter. The effectiveness of these fluorophores as optically responsive dyes for neuronal imaging was assessed by measuring the toxicity and signal‐to‐noise ratio (SNR) of each dye. A great improvement of SNR was obtained when compared to the first‐generation BODIPY‐based voltage sensitive dyes with concomitant toxicity decrease. The mechanism for the optical response is disparate from conventional cyanine‐based dyes, opening up a new way to produce effective voltage sensitive dyes that respond well into the NIR region. Abstract : Rhythm of the Light : Extended donor–acceptor BODIPY derivatives were examined as new optical neuron probes. The dyes were tested by recording the activity of neurons in the stomatogastric ganglion (STG) of the brown crab Cancer pagurus . A simple structure reactivity relationship was derived.